Improving the Quality of Vietnamese Academic Journals on Social Sciences and Humanities: A Commentary on Current Status and Pathways to Internationalization - Trieu Huy Ha (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
This study examines the present status and strategies to improve the quality of Vietnamese academic publications in the fields of social sciences and humanities. The study utilizes a descriptive qualitative design, sourcing data from a recent journal list of Vietnam State Professorships and the ISI/Scopus database while contrasting it with recent developments in regional academic journals across Southeast Asia. This raises concerns regarding the scholarly publication, including traditional publishing methods, the quality of peer review, and issues relating to publication formatting. I propose some solutions to address these problems, facilitating their entry into the international arena for social sciences and humanities. The proposed solutions encompass editorial management, targeting niche publications, publishing exclusively in English, adopting digitalization, and improving editorial awareness. Received 6th May 2024; Revised 5th June 2024; Accepted 8th August 2024